HUBUNGAN ANTARA TINGKAT RELIGIUSITAS DENGAN TINGKAT AKTIVITAS SEKSUAL PADA REMAJA AKHIR - Dya Lita Pradisukmawati; Eko Darminto (Psympathic : Jurnal Ilmiah Psikologi, 2014)
The purpose ofthis study was totest the relationshipbetween thedegree ofreligiousityandthedegree ofsexual activity among late-adolescences. The research design usedwasa quantitative using correlational analysis. The sample was30late adolescentsinthe Southarea ofSurabayawhich wereselectedusing purposive sampling. The subjects of this research were adolescents of aged 18-21 years old, were in/had been in a relationship with another person, lived in South Surabaya, were at Senior High School or University, and were willing to participate in the study. The data were collected using religiousity and sexual activity questionary that were developed by the researcher.Hypothesis was tested using statistical technique Phi correlation coefficient.To know the significant level of correlation analysis result of 0,79, Chi-Squre (X2) was converted with a significant level of 5% , the value obtained was 3.84. Based on these result it can be seen that the Chi-Squre (X2) value of 18.7 is far above the value of theoretical Chi-squre, of 3.84 (5%). From the data in Chi-Squre (X2) crosstab that degree of religiousity have a negative correlational with degree ofsexual activity.